Gelastic Epilepsy and Hypothalamic Hamartoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Three patients with small hypothalamic hamartomas and a recurrent "pressure to laugh," often without actual laughter, are reported from the University of Melbourne, Australia, and McGill University, Canada.